PENGARUH WAKTU AKTIVASI TERHADAP KARAKTERISTIK ADSORBEN DARI KULIT PISANG KEPOK (Musa acuminate L) YANG DIAKTIVASI SECARA FISIKA - Elvitriana; Vera Viena; Muhammad Nizar; Sari Wardani (Jurnal Teknik Kimia USU, 2017)
This study aimed to analyze the effect of activation time on characteristics of banana peels (Musa acuminate L) adsorbent prepared by physics activation. The adsorbent was prepared through two stages, the carbonation of banana skin conducted at 400 oC for 1.5 hours and the physics activation process conducted at 600 oC for 15, 30, and 45 minutes with variations 50 mesh and 100 mesh in size. Adsorbent characteristic parameters analyzed were water content, ash content, volatile matter, fixed carbon, adsorption capacity of iodine, and determination of functional groups using FTIR. Results showed that characteristics of banana peels adsorbent met SNI No. 06-3730-1995 with a water content of 2-8%, 2-9% ash content, 12-17% volatile matter, fixed carbon 73-84% with iodine absorption of 952 mg/g. Results of FT-IR spectra, adsorbent has an absorption band spectra at wave number of 2850 – 2960 cm-1 with stretching vibration appeared on C-H group with intensity 92.50 with activation time of 45 minutes and 50 mesh size. Based on its characteristics analysis, it can be concluded that adsorbent from banana peels has potential to be applied as one of the active carbon absorbent for liquid and gaseous waste.